HUBUNGAN KEBUDAYAAN TORAJA DALAM PRESEPSI KRISTEN - Dating, Dina (Journal of Mandalika Literature, 2022)
Culture is created by God, as it is the essence of Christian faith, in order to reflects His values and glory. Culture can not be separated from the existence of God relate to its origin, process and ultimate objective. However, culture is never be able separated from humanity's oldest struggle, sin. The existence of sin also takes part in various area in the development of human culture, there for brings those who insult and assume that God is not the highest and must be glorified, even rejecting the existence of God. The teachings of the Christian faith explain the concept of redemption which finally enables the culture to recognize the existence of God as the highest being, and to reveal His glory. This paper expresses various Christian struggles in addressing the existence and development of human culture from the perspective of the Christian faith, and returning it to God's original position and purpose for humans.